El despertar de Kumpanam:historia y mito en el marco de un conflicto socioambiental en la Amazonía - Garra, Simone (2012)
In the last years the Awajún people, settled in the Río Cenepa watershed (Department of Amazonas, Peru) are struggling to defend their land from the impact of the mining activities in the Cordillera del Condor mountains. The myth of Kumpanan, an ancestor associated to the homonymous pick, located in the mining area, has been revitalized, with a new meaning, mirroring the current social and environmental contingency of the area. This contributes to rethink the linkages existing between «history» and «myth».